Socialization Of Aedes Sp Birds And Anti-Bird Planting Activities In The Working Way Of Sawah Lebar Puskesmas City Of Bengkulu - Fitri Kurniawati; Nasution, Fitri Handayani; Hartami, Pemi; Ariffin, Rince (Universitas Dehasen Bengkulu, 2025)
Dengue Hemorrhagic Fever (DHF) cases in Bengkulu Village are highly prevalent. Factors contributing to DHF cases include the proliferation of Aedes aegypti mosquitoes, climate, population density, knowledge of disease prevention methods, and social behavior. The use of chemical mosquito repellents can cause health and environmental problems. Citronella plants (Cymbopogon nardus L.) can be extracted as an environmentally friendly repellent. Therefore, the empowerment to produce repellent from Citronella was targeted to the community to improve health and economic benefits. The scope of empowerment consists of health counseling, cultivation and repellent-producing training, and marketing. The results of this program show an increase in knowledge about dengue fever, treatment, disease prevention, and utilization of citronella. The community can also cultivate citronella plants and make bio larvicide products and mosquito repellent sprays from these plants.